Uji Daya Hambat Handsanitizer Dari Daun Sirih (Piper Betle L.) Terhadap Pertumbuhan Bakteri Staphylococcus Aureus - Resky Dwijayanti; Islawati; Asdinar (Jurnal TLM Blood Smear, 2021)
Handsanitizer is one of the antiseptic ingredients in the form of a liquid that is used by the public as a practical hand washing medium. The use of handsanitizers at this time tends to use synthetic and chemical materials so that they have an adverse impact on health and also the environment. Natural materials are safer and also easier to use. One of the results obtained is betel leaf. The antibacterial activity of betel leaf shows that with a 96% ethanol mixture it can inhibit bacterial growth. Betel leaf can be used as an antibacterial because it contains 4.2% essential oil which mostly consists of betephenol which is an isomer ofEuganol allypyrocatechine, Cineol methyl euganol, Caryophyllen (siskuiterpen), kavikol, kavibekol, estragol and terpinen, this study aims to determine the inhibition of betel leaf handsanitizer against the growth of Staphylococcus aureus bacteria. The research design used is a descriptive qualitative laboratory observation research type. The object in the population is Staphylococcus aureus bacteria. The object in the sample is betel leaf (Piper betle L). The method used is to determine the total number of samples needed by using the formula Fereder with a sample calculation result of 23.5. The results obtained from 3 concentrations obtained that the highest bacterial inhibition zone was at a concentration of 30% with an average value of 21mm and the lowest bacterial inhibition zone was at a concentration of 10% with an average value of 13mm. Whereas for the negative control group (-) the average value was 0 and for the positive control group (+) the average value was 34mm. The conclusion from several treatments of betel leaf extract starting from a concentration of 10%, 20%, and 30% can be drawn a conclusion that from the three concentrations tested with 5 times treatment, the results of the betel leaf extract concentration have the highest average value of the inhibition zone. treatment is at a concentration of 30% that is 21mm